Development of Low-Loss Nizn-Based Ferrite Materials for High-Frequency Applications - Yahya, Noorhana (1998)
This work is an initial response to the demand for miniaturisation of electronic circuits and the shift to higher operating frequencies which has led to the development of high-density low-loss ferrites. In order to meet this demand, a number of necessities, such as fine-grained and homogeneous microstructure, low power loss, weak temperature dependencies of losses and of course reasonable cost of production are required. The first part of the work was to develop the required material by manipulation of composition. NiZn-based ferrites with various additives such as MgO, CuO, TiCh, CoO and CaO were chosen and the low loss property was attained. Subsequently, a systematic crucial approach was started to further minimise the losses and to extend the operating frequency range. Green compacts with a particle size average (PSA) of 1.2um, a sintering temperature of about 1140°C and only air atmosphere were needed to reach the research targets. In conclusion, a composition-microstructure design technique has been successfully developed, which is capable of producing ferrite materials with the desired magnetic properties.